Low-molecular-weight heparin from Cu2+ and Fe2+ Fenton type depolymerisation processes - Vismara, Elena; Pierini, Monica; Mascellani, Giuseppe; Liverani, Lino; Lima, Marcelo; Guerrini, Marco; Torri, Giangiacomo (Thrombosis and Haemostasis, 2010)
Hydrogen peroxide (H2O2) and Cu(OAc)2 or FeSO4 (Fenton type reagents) perform heparin (Hep) depolymerisation to low-molecular-weight heparin (LMWH) following a radical chain mechanism. Hydroxyl (OH) radicals which are initially generated from H2O2 reduction by transition metal ions abstract hydrogen atoms on the heparin chain providing carbon centred radicals whose decay leads to the depolymerisation process. The main depolymerisation mechanism involves Hep radical intermediates that cleave the glycosidic linkage at unsulphated uronic acids followed by a 6-O-nonsulphated glucosamine, thus largely preserving the pentasaccharide sequence responsible for the binding to antithrombin III (AT). Both the transition metal ions influence the overall efficiency of the radical chain processes: Fe2+ acting as a catalyst, while Cu2+ acts as a reagent. LMWHs, especially those afforded by Cu2+, are somewhat unstable to the usual basic workup. However, this lack of stability can be eliminated by a previous NaBH4 reduction. Furthermore, with Cu2+, the process is much more reproducible than with Fe2+. Therefore, for the process of Fenton type depolymerisation of heparin, the use of Cu(OAc)2 is clearly preferable to the more “classical” FeSO4. The resulting activities and characteristics of these LMWHs are peculiar to these oxidative radical processes. In addition, LMWH provided by H2O2/Cu(OAc)2 in optimised conditions was found to posses anti-Xa and anti-IIa activities comparable to those of LMWHs currently in clinical use.Footnote: Dedicated to Prof. Pietro Bianchini.
Keywords: Heparin radical; LMWH; Fenton type reaction; transition metal ions; NMR